Beyond Orientalist Discourses: Media and Democracy in Asia - Lee, Chin-Chuan (Javnost-The Public, 2001)
This editorial introduction provides a framework for the later articles. It is concerned to address critically a number of the ways in which the issue of media and democracy in Asia is currently discussed. The sheer variety of the experience of Asia is emphasised, and explanations that seek to account for the past and present shortcomings of democratisation in some Asian countries in terms of general categories are found to be wanting. For example, the use of idea of the influence Confucianism to explain important social phenomena is shown to be insensitive the complexity of the ideas that are lumped together under the single term "Confucianism" and to the evidence both of differences in media behaviour observable in societies undoubtedly influenced by it and to similarities across countries with different backgrounds. The introduction goes on to consider some of the problems about the relationship between state, media, market, globalisation and democracy that remain to be explored in detail. It is pointed out that none of these categories is self-evident, and that one and the same phenomenon can have a different meaning in different social circumstances.